Post-School Transition Challenges for Students with Disabilities in Nepal: Perspective from Disability Interpretive Lens - Shrestha, Sharan Hari; Neupane, Nam Raj; Han, Kyounggun (Education and Development, 2020)
This study attempts to address the issue of post-school transition which is very important yet ignored in the field of special education in Nepal. The study is a qualitative research based on the phenomenological approach using disability interpretive lens. Three special schools from three different districts of Kathmandu valley were selected as sample schools by convenience sampling method. There were 8 respondents in total where 3 were head teachers and 5 were experts; and all the respondents were selected by purposive sampling method. All the head teachers of three special schools of the study area and experts of special education were considered the population of study. Interview guidelines were prepared and validated after reviewing by special education experts. Document study was also another method of data collection and the obtained data are used to support the result of the study. Data triangulation was done to maintain the reliability of the study. The result indicated that there has been a huge gap in understanding and implementing post-school transition in special education of Nepal. The educational policies and documents lack incorporating this segment of educational issue. Schools having IEPs and existing curriculum lack planning on post-school transition. Similarly, lack of disable-friendly school infrastructures, lack of people’s awareness and poverty are also some challenges for effective implementation of post-school transition process. It is very important for concerned authorities and agencies to address this left over vital educational issue in their policies and educational documents as soon as possible.